Clipping of the elements of the gallbladder neck taking into consideration pathomorphological results in patients with acute calculous cholecystitis in combination with chronic viral hepatitis - A. O. Kolotvin; L. I. Kolotvina (Kazimierz Wielki University, 2019)
In abdominal surgery, the problem of combined pathology of the abdominal cavity, which according to WHO, is diagnosed in 30% of patients, is very urgent. Prevention of complications during LCE is one of the important tasks of the ACC treatment, which requires the use of rational modern technical approaches, especially at the stage of clipping elements of the gallbladder neck. The effect of the polymer clips on the tissue is less pronounced and widespread than when using metal clips. All this, especially the absence of the epithelial tissue and the preservation of cells of fibroblasting diferon in the area of application of polymeric clips, will promote the development of conditions for rapid development of the scar tissue there. The stated above demonstrates the safety of polymeric clips, therefore, it is expedient to use them in comorbid patients, namely, in ACC in combination with CVH.